2014
DOI: 10.1186/1475-2875-13-194
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of malaria and anaemia in the Bonikro mining area, central Côte d’Ivoire

Abstract: BackgroundThe epidemiology of malaria and anaemia is characterized by small-scale spatial and temporal heterogeneity, which might be influenced by human activities, such as mining and related disturbance of the environment. Private sector involvement holds promise to foster public health, including the prevention and control of malaria and anaemia. Here, results from a cross-sectional epidemiological survey, conducted in communities that might potentially be affected by the Bonikro Gold Mine (BGM) in Côte d’Iv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 35 publications
7
22
1
Order By: Relevance
“…Additionally, effective malaria control programmes have been shown to significantly reduce anaemia burden, with anaemia now considered a surrogate indicator of impact of malaria control programmes [ 46 , 47 ]. Interestingly in this study, the risk of anaemia decreased with increasing age groups in contrast to the observed increasing risk of malaria across the same age groups in our study and some studies other malaria-endemic settings [ 15 , 35 , 48 ]. However, in all the other settings, the reported malaria parasite carriage rates were significantly higher than the 6.8 % reported in this study.…”
Section: Discussioncontrasting
confidence: 75%
“…Additionally, effective malaria control programmes have been shown to significantly reduce anaemia burden, with anaemia now considered a surrogate indicator of impact of malaria control programmes [ 46 , 47 ]. Interestingly in this study, the risk of anaemia decreased with increasing age groups in contrast to the observed increasing risk of malaria across the same age groups in our study and some studies other malaria-endemic settings [ 15 , 35 , 48 ]. However, in all the other settings, the reported malaria parasite carriage rates were significantly higher than the 6.8 % reported in this study.…”
Section: Discussioncontrasting
confidence: 75%
“…Such impacts are associated with, for example, deforestation that can create ideal breeding grounds for mosquitoes; migration of naive populations to malariaendemic areas, or migration of infected people to areas where the malaria vector is present and transmission, albeit absent or very low, is suitable; a large concentration of workers living in poor housing and thus highly exposed to the vector; and creation of ideal water habitats for mosquito breeding, such as artificial lakes associated with dam construction. These and other consequences of development projects, as well as the negative impacts on health, have been well documented for more than a century (e.g., Cruz 1972;Ghebreyesus et al 1999;Lerer and Scudder 1999;Jackson and Sleigh 2000;Keiser et al 2005a;Knoblauch et al 2014). Nevertheless, they continue to happen and to threaten the lives of many in malaria-endemic areas, exposing major flaws in the transparency and execution of environmental impact assessments (Erlanger et al 2008).…”
Section: Human-made Environmentmentioning
confidence: 99%
“…The prevalence of P. falciparum has declined in the study population between 2010 and 2013. Possible contributors include: (i) a decrease in disease transmission due to interventions, such as ITN distribution (in 2010) and focal indoor residual spraying campaigns [ 23 , 25 , 45 , 46 ]; (ii) the improved diagnostic capacity using RDTs; (iii) an increased availability (including accessibility and affordability) of ACTs in medicine outlets [ 24 , 40 , 47 ]; (iv) environmental changes (e.g., change of vegetation, urbanization, and alteration of breeding sites) [ 48 , 49 , 50 ]; and (v) an increased awareness of, and improved economic conditions to, utilize protective measures [ 51 ]. The national mass-distribution campaign of ITNs was ongoing at the time of the BHS, and a study six months after the distribution found 87.6% of households owned at least one ITN, with 76.5% of households regularly sleeping under an ITN [ 45 ].…”
Section: Discussionmentioning
confidence: 99%